Prevalence, underlying factors and consequences of mobile game addiction in school going children of six to twelve years in Kanyakumari district - V., Arul Prasath S.; Perumal, Bagavathy M.; Samuel, Steeve Gnana (International Journal of Contemporary Pediatrics, 2022)
Background: Children nowadays are heavily engaged with their smartphones with high-quality gaming features. This addiction affects their health, causing physical and psychosocial disabilities. The objective of this study was to find the prevalence, underlying factors and consequences of mobile game addiction among school-going children. Methods: This cross-sectional study, conducted between 1st July to 31st December 2021, enrolled 120 children aged 6 to 12 years old attending the outpatient department of Kanyakumari Government medical college hospital. Results: We found out that male students displayed more addictive behaviour. The primary cause of mobile game addiction was loneliness, length of time spent playing mobile games and using it as their primary source of entertainment. This addiction resulted in headaches, eye and ear discomfort, insomnia, anxiety, depression, and disputes with family members. Conclusions: We found a correlation between video game addiction and psychosocial and physical disabilities. Extensive research is needed to identify gaming patterns leading to addictions and health consequences.